Effectiveness of Participatory Communication on Sustainable Integrative Pesantrenpreneur Program in AHDA Pesantren - Suharti, Bangun (PT. Riset Press International, 2025)
Pondok pesantren have potential actors and factors for the formation of an entrepreneurial climate. This entrepreneurship climate has actually inspired the establishment and development of Pondok pesantren. This is evident from the beginning until the passage of time, pesantren do not get much assistance from the government. This potential, if it receives sufficient financial support, will make pesantren one of the pillars of the nation's economy. This research was conducted using the participatory action research method of the productive waqf futures program in the AHDA pesantren in East Java. Data was obtained through direct action activities, in the term productive waqf program, interviews and intensive, interactive and participatory communication both in offline discussion groups and through Whatsapp groups. The results of this study indicate that the effects obtained in the participatory communication of the pesantrenoreneur program include cognition, affection and behavioral effects. Cognition effect is the knowledge effect, which opens the knowledge of the community group, namely Pesantren Ahda East Java, that they have great potential. The effect of affection is the effect of realizing and opening up insight that a step must be taken to support and realize the program offered. The behavioral effect is obtained that the AHDA pesantren in East Java Indonesia has been able to utilize its internal and external potential to the fullest. This sustainable integrative pesantrepreneur program can be realized and run well and will even continue to be developed sustainably.